Risk of early death after treatment with curative intent for head and neck squamous cell carcinoma: a retrospective population-based study - Bazina, Mahmoud; Nikkilä, Rayan; Haapaniemi, Aaro; Bäck, Leif; Ventelä, Sami; Mäkitie, Antti (MJS Publishing, Medical Journals Sweden AB, 2025)
Background and purpose:
Knowledge regarding the risk factors for early death in patients with head and neck squamous cell carcinoma (HNSCC) is scarce. This study aims to evaluate the rate of early death (during or within 6 months of treatment) and its associated risk factors in HNSCC patients treated with curative intent.
Materials and methods:
A retrospective, population-based analysis of all HNSCC patients (n = 762) treated with curative intent at the Helsinki University Hospital (Helsinki, Finland) during 2012-2015 was conducted. Using the chi-square test, associations between categorical variables were assessed. Univariate and multivariate analyses were performed to identify independent factors for early death.
Results:
The rate of early death was 10.1% with a median age of 70 years at diagnosis. Advanced stage, smoking > 40 pack-years, and heavy alcohol consumption were associated with increased odds of early death. Elevated thrombocyte levels > 380 (x 109L) were observed more frequently in the early-death group when comparing the levels with the late-death group (p < 0.01). However, only age (odds ratio [OR] 1.05; 95% confidence interval [CI]:1.02-1.08), T4 class (OR 5.98; 95% CI: 2.60-13.74), N2 class (OR 2.98; 95% CI: 2.60-13.74), and N3 class (OR 12.24; 95% CI: 2.99-50.19) emerged as independent risk factors for early death.
Interpretation:
Early death risk is increased in older patients and those with advanced-stage HNSCC. Elevated thrombocyte count requires further studies to assess its utility as a potential clinical marker.